Tissue factor is regulated by epidermal growth factor in normal and malignant human endometrial epithelial cells - Kato, Sumie; Pinto, Mauricio; Carvajal, Andrés; Espinoza, Natalia; Monsó, Carolina; Bravo, Loreto; Villalon, Manuel; Cuello, Mauricio; Quest, Andrew F.; Suenaga, Akihiko; Brosens, Jan J.; Owen, Gareth I. (Thrombosis and Haemostasis, 2005)
Tissue Factor (TF), the initiator of the extrinsic coagulation cascade, is overexpressed in a variety of cancers. TF is also expressed in normal human endometrium but little is known about its expression or regulation in endometrial cancer. We demonstrate herein that TF is expressed in the endometrial adenocarcinoma cell line Ishikawa. Furthermore, epidermal growth factor (EGF) induces a rapid and sustained increase in TF expression. Estradiol and progesterone had no effect on basal or EGF-induced TF expression in Ishikawa cells. In contrast to the pronounced and sustained upregulation at the protein level,EGF treatment elicited only a modest and transient increase in TF mRNA levels. This activity corresponded to the response observed from an exogenous TF promoter construct. However, the induction of TF was abrogated by cycloheximide as well as actinomycin-D, inhibitors or protein- and mRNA-synthesis, re-spectively, demonstrating that EGF mediates its effect through activation of the TF gene. Fractionation experiments showed that EGF increases TF presence in caveolin-1 containing membrane fractions. Coagulation and invasion assays were used to explore the physiological implications of TF regulation. The results demonstrate that EGF-mediated induction of TF increases the procoagulant activity and invasive potential of Ishikawa cells. Furthermore, immunocytochemistry confirmed that TF is regulated by EGF in primary cultures of normal endometrial epithelial cells and malignant tumor cells. In conclusion, EGF-mediated upregulation ofTF results in accumulation of this glycoprotein in caveolae-like membrane fractions and increased coagulative and invasive potential. Our results suggest that TF may play an integral role in endometrial carcinogenesis.
Keywords: Endometrium; Ishikawa; coagulation; invasion; caveolin